ENHANCING UTILIZATION OF HEALTH FUNDS INSURANCE THROUGH THE ACCOUNTABILITY CONTROL MODEL - Muhammad Arifai; Zulkarnaini; Dwi Melvinasvita; Yeni Irawan; Mukhlisul Muzahid (CV. Radja Publika, 2023)
The Aceh People's Health Insurance Fund (known as JKA, JaminanKesehatan Aceh) is an investment by the Aceh’s Government in the public health sector that requires continuous monitoring and control to ensure the provision of quality medical services. This study aims to develop an accountability control model in the strategic resource management of JKA, which is considered appropriate to identify the suitable and efficient level of control in managing JKA funds by hospitals in Aceh. The research framework is developed based on theoretical arguments emphasizing the need to utilize an appropriate control model that focuses on monitoring the responsiveness of health care providers to the expectations, desires, and demands of health service users. Additionally, the study also tracks financial and non-financial administration compliance aspects, as well as the achievement of stakeholder missions in the utilization of JKA funds. Despite the integration of JKA funds with the National Health Insurance program under the Social Security Administrating Body, service issues persist, and potential for improvement remains. In this study, the Performance Measurement System (PMS) control model is employed as a moderator of the JKN-JKA hospital control system, which consists of two strategic resources, namely human resource control and physical resource control, with a focus on JKA utilization performance. The utilization of the control model is categorized into two continuums, namely diagnostic control and interactive control. Respondent data were obtained through purposive sampling based on the research objectives. The sample for this research comprises hospitals, health centers, clinics, and optical facilities providing JKA health services in North Aceh and Lhokseumawe City. The study results provide empirical evidence that the utilization of a diagnostic and interactive control model enhances the performance of JKA fund utilization. This finding implies the applicability of the PMS control model for health service providers in Aceh.